Taking the state of court public interest litigation and the public sphere in metropolotan India - Dembowski, Hans (New Delhi Oxford University Press, 2001)
Taking the state of court examines the extent to which public interest litigation makes in-efficient accessible and responsible to the general public. It also offers a Sociological Analysis of Environmental Movements, particularly in Calcutta, as well as
Keywords: Citizen suits (Civil procedure); Public interest; State, the; Public interest law